Analysis and design as bricolage - Edwards, Mogammad Sharief (Department of Information Systems, 2016)
Information Systems in generally acknowledged to be a complex field and many studies over time have quoted significant failure statistics. This paper seeks to answer the question - How to more appropriately evaluate and select information systems design (ISD) methods that better enable successful design outcomes. The research covers literature relating analysis and design, information systems design methods, complexity, ontology and conceptual modelling and how they relate to ISD. This research was conducted within a larger national research project aiming to improve organising practices within IT in organisations. To this end the research followed a participatory action research approach underpinned by systems thinking theoretical perspective. What emerged out of this study was the appreciation for the bricolage that takes during an analysis or design effort - this perspective highlighted the following factors that can enable improved method evaluation and selection, namely: Epistemology, Contextual Influences and Social Action. These factors are shown to operate in dialectic process that if engaged with can provide insight into what an appropriate method can be.